ANALYSIS OF THE IMPLEMENTATION OF GOVERNMENT PUBLIC POLICY COMMUNICATION THROUGH THE STUDENT CREATIVITY PROGRAM (PKM) AT UNIVERSITIES IN LLDIKTI REGION 3 - Taufan Teguh Akbari; Patricia Vicky Sihombing; Cherie Mawuntu; M.Ikom Mayke Angelica; Rio Alfando (Sean Institute, 2023)
Colleges are great places for students to develop their capacities. This is because the role of universities as printers of human resources and their role is increasingly important in the era of Society 5.0. Moreover, the world is increasingly developing where technology changes people's political, social, cultural, and economic constellations e. The skills needed are also growing, including hard and soft skills. Therefore, universities must find effective ways to develop the abilities of their students to have high competitiveness and be innovative and creative in their way of thinking. One way to take is the Student Creativity Program (PKM). The program allows colleges to challenge their students to step out of their comfort zones. PKM makes its students learn to find theoretical and practical innovative ideas. In addition, PKM makes students learn about collaboration, research, strategic planning, and abilities that are relevant today. Although PKM has great benefits, many students are still constrained to get involved. These obstacles include difficulty getting information, sudden program announcements, difficulty getting ideas, difficulty getting supervisors, and difficulty finding a team. The last three challenges are more of a process. What is quite interesting is that there are complaints about the difficulty of obtaining information and sudden announcements. This needs to be highlighted, in a sense in terms of public policy communication. There are many repercussions if PKM is announced within a small deadline. Moreover, PKM is more than just collecting proposals. There is a long process to go through. Therefore, the author reviews how the communication pattern of higher education public policy in communicating this PKM. The author wants to analyze and evaluate the public policy communications carried out. The research focus is universities in LLDikti Region 3 The research approach is qualitative